Analysis of Tenant Selection Criteria in an Emerging Rental Market (Global Journal of Management and Business Research, 2014)
The aim of this paper is to investigate tenant selection criteria adopted by the registered real estate firms and the relationship between the criteria and the firms' years of experience in property management practice, core areas of professional practice and size of the firms with a view to determining the important criteria required of prospective tenant(s) to secure a rental apartment in the developing property market of Metropolitan Ibadan.The study adopts a questionnaire survey. The instruments (Tenant Assessment Checklists) were administered on a sample of estate surveying and valuation firms (registered real estate firms). Data collected were analysed using discriptive statistics, factor analysis, cluster analysis and chi-square.
Keywords: tenant selection; criteria; real estate firm; profiles; ibadan